Protective Effect of Propolis Extract Against Lead Acetate Toxicity in Mice (Mus Musculus) Testes - Widawati, Tuti; Sudjarwo, Sri Agus; Hermadi, Herry Agoes (KnE Life Sciences, 2017)
This study was aimed to investigate the protective effect of propolis extract from Apis mellifera that was obtained from Agro Tawon Rimba Raya Malang against the exposure of lead acetate 20 mg/kgBW orally. Twenty-five BALB/C mice were randomly devided into five groups. Negative control received only CMC-Na 1.5 % and Tween 80 0.5% also aquadest an hour after the first administration; Positive control group that administered CMC-Na 1.5 % and Tween 80 0.5% then continued received 20 mg/kgBW of lead acetate, Treatment group was received 200; 400 and 800 mg/kgBW of propolis first and then an hour after that received 20 mg/kgBW of lead acetate. The treatment was conducted for 7 days of adaptation and 35 days of treatment. At the end of the research all mice were sacrificed and testes were collected. Testes tissue were processed using Hematoxylin-Eosin staining. The result showed that an increase of spermatocyte, spermatid and sertoli cell compare to group that only received lead acetate, but thickness of seminiferous tubules epithelium showed slighly similar in all groups. Key words : propolis, lead, reactive oxygen species, free radical, testes